PEMANFAATAN UBI MBOTHE SEBAGAI PRODUK UMKM DI DESA DRUJUGURIT KECAMATAN NGIMBANG KABUPATEN LAMONGAN - Nawari Nawari; M. Hafidh Nashrullah; Vegi Ayu Indah; Siti Nur Alifiyah; Shofa’atul Muniroh (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
The aim of this work program is to change the mindset of residents about the potential of mbote which can be developed with contemporary innovations so that consumers are more interested and able to compete in beautiful packaging. The activity method used is action review. The results of the study found that there was a lack of village communities in entrepreneurship activities by utilizing village potential. Therefore, this assistance is an innovation for mbote traders to help trigger the production of MSME mbote chips to make them more attractive and easy for consumers to remember. In addition, the results of this assistance were also able to increase the enthusiasm of the Drujugurit village community in making the mbote chip business which was originally ordinary to become even more enthusiastic in producing mbote chips.Keywords: you can list 3-5 keywords seperated with coma. (in Times New Roman (Headings) with 10 font size, single spacing and italized)